How can brand equity for tourism destinations be used to preview tourists’ destination choice? An overview from the top of Tower of Babel - Francisco Dias (Tourism & Management Studies, 2017)
Customer-based brand equity for tourism destinations (CBBE-TD) is a helpful construct to assess destination branding effectiveness. However, it would be even more useful if it could be integrated into a wider methodological approach articulating destination brand assessment with the destination choice process. This paper describes a new research programme – Favourite Destinations Worldwide – that includes three interrelated innovative tools: (1) the destination brand choice model that allows a better conceptualization of CBBE-TD in the context of destination choice; (2) the Tower of Babel platform, a multilingual online survey for data gathering, to assess CBBE-TD of all destinations competing in the world market; and (3) the Destination Brand Gnosis, a propriety software for qualitative data analysis, transforming the meta-data into a system for constantly evaluating brand attractiveness. Additionally, for illustrative purposes empirical data from two national samples is presented: Portuguese (N = 524) and Brazilian (N = 955). Besides presenting the preferred destination brands for Brazilian and Portuguese tourists, the results confirm a basic assumption supporting this research program related to the geographic polarization of the most valued destination brands: “dream destination brands” correspond to destinations located farther from respondents’ home-places, in other continents, requiring long-haul air travel, while “favourite destination brands” are predominantly destinations located nearer, in respondents’ own countries or neighbouring countries.